Water-Rich Soft Soil Freezing Method Combined With Steel Sleeve Receiving-Shield Technology Field Test Research - Mei, Y.; Liu, Y. Y.; Yan, X.; Liang, C.; Zhu, J. T. (Frontiers in Earth Science, 2022)
The initiation and reception of shields are major risk events for shield construction in water-rich and weak strata. Although the freezing method and the steel sleeve method receiving-shield tunneling technologies both have engineering applications, the environmental safety control effect cannot meet the construction requirements of water-rich soft soil. Considering the shield construction of a typical soft soil layer in Suzhou, China, as a research target, the applicability and safety of the freezing method combined with steel sleeve receiving-shield technology in water-rich soft soil were evaluated based on a field test system. The test results show that, during soil freezing, the temperature change trend of each measuring point in the temperature measuring hole is roughly the same. The freezing process can be divided into five typical stages. The closer the active freezing period of the water-rich soft soil is to the inside of the frozen-soil curtain, the faster the development rate of the frozen wall. The soil cooling gradient increased with an increase in the radial depth. After freezing the curtain circle, the soil frost heave significantly accelerated until the frost heave amount peaked. During the construction process, special attention should be paid to the change in the value of the soil settlement during each stage change to prevent sudden changes in soil displacement. The freezing method, combined with steel sleeve receiving-shield technology, can effectively reduce the environmental disturbance caused by shield construction in water-rich soft soil.